1990
DOI: 10.1111/j.1365-2125.1990.tb03843.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cholestyramine and activated charcoal on glipizide absorption.

Abstract: 1 The interference of cholestyramine and activated charcoal with the absorption of glipizide was studied. 2 In a cross-over study comprising three phases, single doses of cholestyramine (8 g

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…The drug interaction potential for colesevelam is considered low compared to that for conventional BA sequestrants. This is based on the observation that, although many drugs have been shown to interact with the conventional BA sequestrants (eg, fluvastatin, 19 digoxin, 27 warfarin, 28 glipizide, 29 hydrochlorothiazide, 30 propanolol, 31 frusemide, 32 ezetimibe, 33 hydrocortisone, 34 diclofenac, 35 sulindac, 36 and valproate 37 ), pharmacokinetic studies demonstrated that colesevelam does not interact with any of the drugs tested (digoxin, metoprolol, quinidine, valproic acid, warfarin, fenofibrate, lovastatin, and verapamil) 21 – 23 with the possible exception of verapamil. Importantly, this list includes some of the same drugs that did show an interaction with conventional BA sequestrants (ie, digoxin, warfarin, and valproate) 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The drug interaction potential for colesevelam is considered low compared to that for conventional BA sequestrants. This is based on the observation that, although many drugs have been shown to interact with the conventional BA sequestrants (eg, fluvastatin, 19 digoxin, 27 warfarin, 28 glipizide, 29 hydrochlorothiazide, 30 propanolol, 31 frusemide, 32 ezetimibe, 33 hydrocortisone, 34 diclofenac, 35 sulindac, 36 and valproate 37 ), pharmacokinetic studies demonstrated that colesevelam does not interact with any of the drugs tested (digoxin, metoprolol, quinidine, valproic acid, warfarin, fenofibrate, lovastatin, and verapamil) 21 – 23 with the possible exception of verapamil. Importantly, this list includes some of the same drugs that did show an interaction with conventional BA sequestrants (ie, digoxin, warfarin, and valproate) 23 .…”
Section: Discussionmentioning
confidence: 99%
“…A secondary goal is the return of euglycemia in patients who develop hypoglycemia. Patients with recent acute sulfonylurea overdoses should receive activated charcoal if mental status is deemed adequate [13]. Carbohydrate-containing food can be provided to patients if they are awake and alert enough to eat and protect their airway.…”
Section: Clinical Management: Prevention and Initial Management Of Hymentioning
confidence: 99%
“…Inhibition of glipizide metabolism by trimethoprim-sulfamethoxazole is also assumed, but drug concentrations have not been measured (JOHNSON and DOBMEIER 1990). Intake with cholestyramine reduces glipizide absorption by 29% and with activated charcoal by 81 %, so that the latter may be taken in acute overdose situations (KIVISTÖ and NEUVONEN 1990). As with other sulfonylureas, absorption of glipizide can be enhanced with antacids such as sodium bicarbonate and magnesium hydroxide, but not aluminum hydroxide (KIVISTÖ and NEUVONEN 1991a,b).…”
Section: /) Pharmacokinetic Interactionsmentioning
confidence: 98%